2010
DOI: 10.1007/s00535-010-0247-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of metabolic syndrome is comparable between inflammatory bowel disease patients and the general population

Abstract: Prevalence of metabolic syndrome in our IBD patients was comparable to that of the general population. Because age was the independent risk factor for developing MS, evaluation for MS is needed for elderly IBD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 32 publications
1
26
0
1
Order By: Relevance
“…21,22 Overnutrition (and as a consequence obesity) is now encountered in an increasing proportion of patients with IBD, as it is in the general community. 23 The interest in obesity has been amplified by the concept that mesenteric fat might drive intestinal inflammation in patients with Crohn's disease. 24 Whether obesity is indeed associated with an adverse natural history is currently unclear from the literature, although obesity is likely to affect surgical complexity and morbidity.…”
Section: Protein and Energy Statusmentioning
confidence: 99%
“…21,22 Overnutrition (and as a consequence obesity) is now encountered in an increasing proportion of patients with IBD, as it is in the general community. 23 The interest in obesity has been amplified by the concept that mesenteric fat might drive intestinal inflammation in patients with Crohn's disease. 24 Whether obesity is indeed associated with an adverse natural history is currently unclear from the literature, although obesity is likely to affect surgical complexity and morbidity.…”
Section: Protein and Energy Statusmentioning
confidence: 99%
“…An interesting example of intra-abdominal fat accumulation in subjects free of metabolic disease7 and who are frequently underweight is Crohn's disease (CD), a chronic relapsing inflammatory process that can affect any part of the gastrointestinal tract 8. In the first description of this disease, Crohn et al reported the peculiar presence of an enlarged mesenteric adipose tissue that envelops more than half of the intestinal circumference in corresponding inflammatory lesions 8 9.…”
Section: Introductionmentioning
confidence: 99%
“…The most current investigations have been directed toward the identification of metabolic syndrome among individuals with IBD, with prevalence rates ranging from 7.1 to 17.7% among patients with CD and 16.0 to 29.5% among those with UC (25,34,47) . However, the prevalence of metabolic syndrome varies widely depending on the criteria employed and the WC is one of the variables used to define this condition.…”
Section: Discussionmentioning
confidence: 99%